Seismic Full‐Waveform Inversion of the Crust‐Mantle Structure Beneath China and Adjacent Regions. Issue 9 (19th September 2022) - Ma, Jincheng; Bunge, Hans‐Peter; Thrastarson, Solvi; Fichtner, Andreas; Herwaarden, Dirk‐Philip van; Tian, You; Chang, Sung‐Joon; Liu, Tingting
Abstract: We present the first‐generation full‐waveform tomographic model ( SinoScope 1 . 0 ) for the crust‐mantle structure beneath China and adjacent regions. The three‐component seismograms from 410 earthquakes recorded at 2, 427 stations are employed in iterative gradient‐based inversions for three successively broadened period bands of 70–120 s, 50–120 s, and 30–120 s. Synthetic seismograms were computed using GPU‐accelerated spectral‐element simulations of seismic wave propagation in 3‐D anelastic models, and Fréchet derivatives were calculated based on an adjoint‐state method facilitated by a checkpointing algorithm. The inversion involved 352 iterations, which required 18, 600 wavefield simulations. SinoScope 1 . 0 is described in terms of isotropic P‐wave ( V P ), horizontally and vertically polarized S‐wave velocities ( V SH and V SV ), and mass density ( ρ ), which are independently constrained with the same data set coupled with a stochastic L‐BFGS quasi‐Newton optimization scheme. It systematically reduced differences between observed and synthetic full‐length seismograms. We performed a detailed resolution analysis by repairing input random parametric perturbations, indicating that resolution lengths can approach the half propagated wavelength within the well‐covered areas. SinoScope 1 . 0 reveals strong lateral heterogeneities in the lithosphere, and features correlate well with geological observations, such as sedimentary basins, Holocene volcanoes, Tibetan Plateau, Philippine Sea Plate, and various tectonic units. The asthenosphere lies below the lithosphere beneath East and Southeast Asia, bounded by subduction trenches and cratonic blocks. Furthermore, we observe an enhanced image of well‐known slabs along strongly curved subduction zones, which do not exist in the initial model. Plain Language Summary: Subduction (a geological process where the oceanic lithosphere descends into the Earth's mantle at convergent boundaries) has been the dominant plate‐tectonic process in the broad Asian region since the Mesozoic (252–66 million years ago). The nature of cold subducting slabs and hot mantle flows can record and affect the tectonic evolution of the overriding lithospheric plates. In this study, we conduct the full waveform inversion on a large data set to image the crust‐mantle structure of this region. The computationally demanding simulations were performed on two of the world's fastest supercomputing facilities. Our new model delivers seismic illumination of the region at unprecedented resolution and exhibits sharper and more detailed shear wave velocity structure in the lithosphere with greatly improved correlations with surface tectonic units compared to previous tomographic models. The narrow low‐velocity layer (generally referred to as asthenosphere) below the lithosphere is present beneath East and Southeast Asia, bounded by subduction trenches and cratonic blocks. The continuous and intense subduction processes are responsible for high‐velocity anomalous bodies in the mantle and the formation of the asthenosphere mentioned above. Key Points: We construct a new full‐waveform tomographic model of the broad Asian region for 30–120 s period via adjoint and spectral‐element methods The resolution analysis shows reasonably good resolution in the frequency band of interest and limited trade‐offs between model parameters Our model shed new light on the subsurface behavior of cold subducting slabs & hot mantle flows and their relation to the overriding plates